Global Aspects of Complex Geometry - Catanese, Fabrizio; Esnault, Hélène; Huckleberry, Alan; Hulek, Klaus; Peternell, Thomas (Springer Berlin Heidelberg : Imprint: Springer, 2006)
This collection of surveys present an overview of recent developments in Complex Geometry. Topics range from curve and surface theory through special varieties in higher dimensions, moduli theory, Kähler geometry, and group actions to Hodge theory and characteristic p-geometry. Written by established experts this book is a must for mathematicians working in Complex Geometry.